Stevia (Stevia rebaudiana) extract ameliorates insulin resistance by regulating mitochondrial function and oxidative stress in the skeletal muscle of db/db mice - Jin-Young Han; Miey Park; Hae-Jeung Lee (BMC, 2023)
Abstract Background Type 2 diabetes mellitus (T2DM), a growing health problem worldwide, is a metabolic disorder characterized by hyperglycemia due to insulin resistance and defective insulin secretion by pancreatic β-cells. The skeletal muscle is a central organ that consumes most of the insulin-stimulated glucose in the body, and insulin resistance can damage muscles in T2DM. Based on a strong correlation between diabetes and muscles, we investigated the effects of stevia extract (SE) and stevioside (SV) on the skeletal muscle of diabetic db/db mice. Methods The mice were administered saline, metformin  (200 mg/kg/day), SE (200 and 500 mg/kg/day), and SV (40 mg/kg/day) for 35 days. During administration, we checked the levels of fasting blood glucose twice a week and conducted the oral glucose tolerance test (OGTT) and insulin tolerance test (ITT). After administration, we analyzed serum biochemical parameters, triglyceride (TG), total cholesterol (TC), insulin and antioxidant enzymes, and the cross-sectional area of skeletal muscle fibers of db/db mice. Western blots were conducted using the skeletal muscle of mice to examine the effect of SE and SV on protein expression of insulin signaling, mitochondrial function, and oxidative stress. Results SE and SV administration lowered the levels of fasting blood glucose, OGTT, and ITT in db/db mice. The administration also decreased serum levels of TG, TC, and insulin while increasing those of superoxide dismutase (SOD) and glutathione peroxidase (GPx). Interestingly, muscle fiber size was significantly increased in db/db mice treated with SE500 and SV. In the skeletal muscle of db/db mice, SE and SV administration activated insulin signaling by increasing the protein expression of insulin receptor substrate, Akt, and glucose transporter type 4. Furthermore, SE500 administration markedly increased the protein expression of AMP-activated protein kinase-α, sirtuin-1, and peroxisome proliferator-activated receptor-γ coactivator-1α. SV administration significantly reduced oxidative stress by down-regulating the protein expression of 4-hydroxynonenal, heme oxygenase-1, SOD, and GPx. In addition, SE500 and SV administration suppressed the expression of apoptosis-related proteins in the skeletal muscle of db/db mice. Conclusion SE and SV administration attenuated hyperglycemia in diabetic mice. Moreover, the administration ameliorated insulin resistance by regulating mitochondrial function and oxidative stress, increasing muscle fiber size. Overall, this study suggests that SE and SV administration may serve as a potential strategy for the treatment of diabetic muscles.